Water Challenges and Sustainable Solutions for the Promotion of the Green Hydrogen Industry in the Tacna Region, Peru - De Cossío Klüver, Manuel (2024)
In the following article, I put forward several ideas that address the promotion of the green hydrogen industry in the region of Tacna, Peru, considering the water challenges and the need to find alternative sources of fresh water. The promotion of the green hydrogen industry in this region is approached in a comprehensive manner, considering the challenges and sustainable solutions related to water scarcity. Turning to alternative sources of water could also reduce scarcity and alleviate pressures on groundwater and other natural water bodies. Aquifer recharging from alternative sources, which allows water to move from surface water to groundwater, is a well-known process for preventing water shortages.